Answer:
The exponential equation is y = -2×(1/2)^x
Step-by-step explanation:
Ok we have a couple things to note here:
1) The horizontal asymptote of the function is the x axis (always nice)
2) At x=0, y=-2 (i.e, this function will be multiplied by -2 bc the exponent part will transform into one at x=0)
3) Then we need to ascertain the base of the exponential. Based on the facts that at x=1, y=-1 and the "a-value" is -2, we can set up an equation to find b:
y=a×b^x----> -1 = (-2)(b) ------> b=1/2
Therefore, the exponential equation is y = -2×(1/2)^x
Test:
At x = 0, y= -2
At x = -1, y = (-2)*(1/2)^-1 = (-2)*2 = -4
At x=2, y = (-2)*(1/2)^2= (-2)*(1/4) = -1/2
Thus we can be quite certain that this is correct
Answer:
Which expression is equivalent to 5(4x+3)-2x?a 18x+15b 18x+3c 7x+8d 2x+8
A-18x+15
7/4
4 goes into 7 one time.
3 left over.
1 3/4
Answer:
Then value is 2
Step-by-step explanation:
standard of quadratic is A
+Bx+C=0
and 2 is where C is.
sorry for the bad explanation but, trust me I did this type of question in class yesterday
RS Bisects QT means, it cuts QT in two equal halves, so QP would be equal to PT, as it is an isosceles triangle, one other side would be equal as well, so RP is equal to PS, Now, by ASA, we conclude the both mentioned triangles in the figure are congruent.
Hope this helps!